How Is the Audit Market Affected by Characteristics of the Nonaudit Services Market? - FRIEDMAN, HENRY L.; MAHIEUX, LUCAS (Journal of Accounting Research, 2021)
ABSTRACT How can features of the markets for audit and nonaudit services (NAS) affect an audit firm's incentives to invest in audit quality, average audit quality, and social welfare? We address these questions in a model focusing on competition in both audit and NAS markets. We show that, when audit and NAS demand are positively correlated, prohibiting auditors from providing NAS to audit clients leads to higher investments in audit quality, but can decrease average audit quality if marginal clients switch to lower quality auditors. The effect on social welfare can be positive or negative, depending on the distribution of clients' service demands. General bans on auditor provision of NAS can, via similar channels, increase or decrease audit quality and social welfare. Overall, our findings suggest a more nuanced view of how regulating an auditor's provision of NAS might affect audit quality and social welfare, and are driven by the effects of multimarket competition on the auditor's incentives to invest in audit quality, rather than previously identified auditor independence or knowledge spillover channels.